Effect of Dietary P-chitosan levels on Survival and Growth of Fingerlings of Cyprinus carpio, Catla catla and Cirrhinus mrigala B. - B., Victor; U., Ramesh; M., Maridass (Fishery Technology, 2025)
A feeding experiment on the fingerlings of Cyprinus carpio, Catla catla and Cirrhinus mrigala was conducted for 28 day period with four experimental diets added with graded levels of P-chitosan (1,2,5 and 10%) and a control diet which contained 31% crude protein, 7.96% crude fat, 25% crude carbohydrate and 5% crude fibre. Fish fed with the diet containing 1, 2 and 5% P-chitosan had the highest survival, feeding rate and weight gain. The above studies indicate that p-chitosan has growth promoting effect in carps and the inclusion of low levels of P-chitosan (1-2%) in artificial diets is likely to improve carp production.